Oxidants, Oxidative Stress and Role of Phytoantioxidants as Photoprotectives - A Review - Garg, Chanchal; Garg, Munish (Indian Journal of Natural Products, 2019)
Photoaging is a multifactorial process which is attributed mainly to the degree of sun exposure and the amount of melanin present in the skin. The elemental root of skin aging is the generation of free radicals i.e. reactive oxygen species (ROS) and the oxidative stress. This oxidative stress highly affects the skin as it is rich in lipids, proteins, carbohydrates, DNA etc. Although, it has been well demonstrated that the skin has its own exceptionally effective natural antioxidant defence mechanism which is supported by variety of antioxidant enzymes such as peroxidases, catalases and glutathione, yet, the protection exhibited by them is restricted due to overproduction of reactive oxygen species, leading to skin aging. Antioxidant ability of phytoconstituents extracted from various plants minimise the deleterious effects of reactive oxygen species and restrains the clinical manifestations of skin aging. Antioxidant substances, like vitamin E, ascorbic acid, coenzyme Q10, flavonoidal or polyphenolic compounds present in plant extracts and various combinations of these, when applied topically, helps in retaining the skin antioxidant pool, thereby strengthening the skin antioxidant defence mechanism, thus minimising the deleterious effects of free radicals and oxidative stress. Antioxidant compounds like tetrahydro curcuminoids derived from roots of Curcuma longa not only prevents the free radical generation but also counteract the existing free radicals, Acai palm contain anthocyanins which helps in reducing the UVB induced DNA damage. Likewise, polyphenols present in green tea effectively inhibits the free radicals and alter the aging process. Thus, antioxidants, having free radical scavenging potential play a significant role in the prevention and treatment of conditions related to generation of free radicals. This review discusses about the various oxidants (reactive oxygen species or free radicals) formed, oxidative stress caused due to these free radicals and their mechanisms in photoaging. It also reviews the role of various antioxidants particularly, phytoantioxidants in the oxidative stress induced Photoaging and its future potential.
Keywords: Photoaging; oxidative stress; phytoantioxidants; medicinal plants